Pusat Pendidikan Anak Usia Dini Di Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Abdul Muttaqin; Ratna Amanati; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Early childhood is a golden period in human development, because at this time began to be formed and expanded child competence development, both cognitively, emotionally and socially. One of the means that can support the development of children through early childhood education institutions. The Early Childhood Education Center in Pekanbaru will facilitate means of education such as classrooms, means of supporting such a garden nursery, children's play area, art space, performance space as well as a hall area. The child has its own character with different adults. The character of the child, active, creative, and do not like to be restricted cause the necessity of processing specifically against the arrangement of space to accommodate children's activities. With that to optimize The Early Childhood Education Center in Pekanbaru used architectural approach behavior. So there will be formed a good relationship between the function of space and user behavior. The basic idea in the formulation of the concept of the Design Center for early childhood education is derived from the character of early childhood behavior, where early childhood is the period of the free developing imagination and creativity. The application of the concept is applied to the arrangement of masses of buildings, building forms, circulation, structuring of space inside and outside spaces, as well as the facade of the building in accordance with the character of the child.Keyword: The Early Childhood Education Center, Pekanbaru, Architecture of Behavior.